In Vivo Bioluminescent Monitoring of Therapeutic Efficacy and Pharmacodynamic Target Assessment of Antofloxacin against Escherichia coli in a Neutropenic Murine Thigh Infection Model - Zhou, Yu-Feng (Antimicrob Agents Chemother, 2017)
Antimicrobial resistance among uropathogens has increased the rates of infection-related morbidity and mortality. Antofloxacin is a novel fluoroquinolone with broad-spectrum antibacterial activity against urinary Gram-negative bacilli, such as Escherichia coli. This study monitored the in vivo efficacy of antofloxacin using bioluminescent imaging and determined pharmacokinetic (PK)/pharmacodynamic (PD) targets against E. coli isolates in a neutropenic murine thigh infection model. The PK properties were determined after subcutaneous administration of antofloxacin at 2.5, 10, 40, and 160 mg/kg of body weight. Following thigh infection, the mice were treated with 2-fold-increasing doses of antofloxacin from 2.5 to 80 mg/kg administered every 12 h. Efficacy was assessed by quantitative determination of the bacterial burdens in thigh homogenates and was compared with the bioluminescent density. Antofloxacin demonstrated both static and killing endpoints in relation to the initial burden against all study strains. The PK/PD index area under the concentration-time curve (AUC)/MIC correlated well with efficacy (R(2) = 0.92), and the dose-response relationship was relatively steep, as observed with escalating doses of antofloxacin. The mean free drug AUC/MIC targets necessary to produce net bacterial stasis and 1-log(10) and 2-log(10) kill for each isolate were 38.7, 66.1, and 147.0 h, respectively. In vivo bioluminescent imaging showed a rapid decrease in the bioluminescent density at free drug AUC/MIC exposures that exceeded the stasis targets. The integration of these PD targets combined with the results of PK studies with humans will be useful in setting optimal dosing regimens for the treatment of urinary tract infections due to E. coli.